Passenger Loyalty Analysis: Case Study on Indonesian Commuter Trains - Nazwirman Nazwirman; Zainal Zawir Simon (Faculty of Economic and Business, 2020)
This study was aim is to analyze and describe passenger loyalty influenced by the desired service quality performance and satisfaction at PT Kereta Commuter Indonesia (KCI). A sample consisting of 198 respondents was selected based on the particular criteria. The analysis method used was Satistical Package for Social Science (SPSS) version 24 and Analysis of Moment Structure (AMOS) version 22. The results obtained from three hypotheses revealed that the performance of service quality influenced significantly on satisfaction. The service quality performance influenced loyalty significantly. Satisfaction significantly influences loyalty. The customer satisfaction mediated the significance influence of service quality dimensions toward loyalty of the customers. Important dimension in this study were that KCI officers were disposed to help if needed; passengers had a positive attitude; and KCI was the main choice rated by respondents. This study provided theoretical and managerial contribution for marketing service feild. In terms of theoretical implications, each dimension of the performance of service quality could show different levels of the effect toward consumer behavior and was able to offer significant contribution for a company.